Analysis of The Relationship Between Personal Competencies and Individual Work Performance with Job Specialization, Formalization, and Centralization as Moderators - Adihardja, Hamdani Sulaeman; Hendarsjah, Hidajat (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2020)
Abstract. This research examines the impact of personal competencies on individual work performance when performing maintenance activities and examines job specialization, formalization, and centralization as moderator variables. For the analysis, we use questionnaires data from 741 respondents of maintenance officers in the Signalling and Telecommunication Departement at PT KAI (Persero). The results showed that personal competencies significantly affecting individual work performance with a correlation value of 0.001 ( <0.05), and other results related to job Specialization and Centralization as moderator variables demonstrated that these two variables could not be treated as moderators in strengthening the relationship between personal competencies and performance. The results showed correlation value of 0.847 ( >0.05) and 0. 173 (>0.05), respectively. This research's formalization variable was not used in the hypothesis testing stage as a moderator because it lacked instrument validity. This study recommends that maintenance officers have better individual work performance when management focuses on increasing the personal competencies or focuses on increasing competencies in work fields that require special skills by the scope of work they face.Keywords: Personal Competencies. Individual Work Performance. Job Specialization. Formalization. Centralization